Clinical Features of Acute Ischemic Stroke Patients with Hypoesthesia as an Initial Symptom - Takayoshi Akimoto; Katsuhiko Ogawa; Makoto Hara; Satoko Ninomiya; Masaki Ishihara; Akihiko Morita; Satoshi Kamei; Hideto Nakajima (MDPI AG, 2023)
This study aimed to evaluate the clinical characteristics of acute ischemic stroke (AIS) patients who experienced hypoesthesia as the initial symptom. We retrospectively analyzed the medical records of 176 hospitalized AIS patients who met our inclusion and exclusion criteria and evaluated their clinical features and MRI findings. Among this cohort, 20 (11%) patients presented with hypoesthesia as the initial symptom. MRI scans of these 20 patients identified lesions in the thalamus or pontine tegmentum in 14 and brain lesions at other sites in 6. The 20 hypoesthesia patients had higher systolic (p = 0.031) and diastolic blood pressure (p = 0.037) on admission, and a higher rate of small-vessel occlusion (p < 0.001) than patients without hypoesthesia. The patients with hypoesthesia had a significantly shorter average hospital stay (p = 0.007) but did not differ significantly from those without hypoesthesia in National Institutes of Health Stroke Scale scores on admission (p = 0.182) or the modified Rankin Scale scores for neurologic disability on discharge (p = 0.319). In the patients with acute onset hypoesthesia, high blood pressure, and neurological deficits were more likely to be due to AIS than other causes. Since most of the lesions in AIS patients with hypoesthesia as the initial symptom were found to be small, we recommend performing MRI scans with such patients to confirm AIS.